Effectiveness of mulligan mobilization and kinesio-taping technique on the anterior innominate dysfunction in females - Sundas Farooq; Saima Zahid; Sana Hafeez; Danish Hassan (Journal of the Pakistan Medical Association, 2021)
Abstract Objective: The purpose of this study was to determine the effects of Mulligan mobilization with Kinesio Tex tape on pain and disability in anterior innominate dysfunction in females. Methodology: This study was a Quasi Experimental Trial, conducted at Allied hospital and Javeed Medical complex Faisalabad. A sample size of 30 females with anterior innominate dysfunction meeting the inclusion criteria were divided into two groups. Group A was treated with therapeutic ultrasound, Mulligan mobilization technique and kinesio taping technique and group B was treated with therapeutic ultrasound and Mulligan mobilization technique. Data was taken at first day and after 10 days to measure pain and disability by Visual analogue scale and Modified Oswestry Disability Questionnaire (MODQ). Data analysis was done through the SPSS 20. Result: Mean age of group A and B was 32.80±6.02, 34.20±6.51 respectively. Both groups showed significant improvement in pain and disability after the treatment in term of VAS and MODQ respectively. In comparison of two groups, group A showed better improvement in disability MODQ (p=0.004) as compared to VAS (p=0.20). Conclusion: Both Mulligan mobilization along with Kineso tex tape and Mulligan mobilization alone are effective in reducing pain and disability. Mulligan mobilization along with Kinesio tex tape showed significantly better improvement in pain and disability as compared to Mulligan mobilization alone. Key Words: Sacroiliac joint dysfunction, anterior innominate dysfunction, Kinesio taping, Mulligan mobilization, therapeutic ultrasound, Modified Oswestry Disability Questionnaire. Continuous...